2022
DOI: 10.1155/2022/6519712
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, Cytotoxic, and Antimicrobial Evaluation of Tribulus terrestris L., Typha domingensis Pers., and Ricinus communis L.: Scientific Evidences for Folkloric Uses

Abstract: Many medicinal plants have been utilized for centuries despite the lack of scientific evidence of their therapeutic effects. This study evaluated the phytochemical and dual biological profiling, namely, antibacterial and cytotoxic properties, of three plant species, namely, Tribulus terrestris L., Typha domingensis Pers., and Ricinus communis L., in order to explore potential relationships (if any) with their ethnopharmacological uses. GC-MS was used to achieve phytochemical screening of two plant extracts (T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Moreover, HPLC analysis showed that the major compound of TT was acetylsalicylic acid, in both ethanol and methanol extracts. The results of HPLC analysis of the chemical compounds in the extracts of TT in the current study agree with [ 1 , 2 ], who found that TT contains many pharmacologically active components belonging to flavonoids and phenols. However, the chemical composition of the extract varies depending on the extraction method and plant parts [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, HPLC analysis showed that the major compound of TT was acetylsalicylic acid, in both ethanol and methanol extracts. The results of HPLC analysis of the chemical compounds in the extracts of TT in the current study agree with [ 1 , 2 ], who found that TT contains many pharmacologically active components belonging to flavonoids and phenols. However, the chemical composition of the extract varies depending on the extraction method and plant parts [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Medicinal herbal and aromatic plants have been a gaining interest in recent years as feed additives in poultry. Medicinal herbs can alter the active compounds in final products depending on the part used (e.g., seed, leaf, root, or bark) and the processing technique (e.g., extraction with non-aqueous solvents) [ 1 , 2 ]. Several studies in recent years have shown that the use of medicinal herbs as feed additives can improve the health, performance, and nutrient digestibility of broiler chickens [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxicity assays at the cellular level can be useful to reveal the potential risks associated with herbal extracts, [32] and also allow identification, analyses and test on a wide range of bioactive natural compounds. These efforts precede drug discovery and development of new anticancer agents, without adverse effects on normal healthy cells which is always limit the use of many anticancer drugs [33–35] . Cytotoxicity assays (CTAs) of herbal medicines are dependent on the concentration, mechanism of cytotoxicity, evaluation methods, cell type, components and exposure over time [36–39] .…”
Section: Introductionmentioning
confidence: 99%
“…Its biological activity has been related to steroidal saponinsby inducing an apoptotic pathway in breast cancer cells. Trans-N-feruloyl-3-hydroxytyramine and trans-N-feruloyl-3-ethoxytyramine, have been shown to trigger apoptosis in leukemic cancer cells [8][9][10] .…”
mentioning
confidence: 99%